2022
DOI: 10.1177/17534666221140972
|View full text |Cite
|
Sign up to set email alerts
|

The role of autophagy in idiopathic pulmonary fibrosis: from mechanisms to therapies

Abstract: Idiopathic pulmonary fibrosis (IPF) is an interstitial pulmonary disease with an extremely poor prognosis. Autophagy is a fundamental intracellular process involved in maintaining cellular homeostasis and regulating cell survival. Autophagy deficiency has been shown to play an important role in the progression of pulmonary fibrosis. This review focused on the six steps of autophagy, as well as the interplay between autophagy and other seven pulmonary fibrosis related mechanisms, which include extracellular mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 189 publications
1
15
0
1
Order By: Relevance
“…To further investigate how lactate promotes fibroblast activation, we examined the status of the NF-κB signaling pathway. It is known that the transcription of P65 is necessary for the expression of fibrosis-related markers [ 43 45 ], and P65 is a transcription factor activated downstream of ROS [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate how lactate promotes fibroblast activation, we examined the status of the NF-κB signaling pathway. It is known that the transcription of P65 is necessary for the expression of fibrosis-related markers [ 43 45 ], and P65 is a transcription factor activated downstream of ROS [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that autophagy plays a key role in the pathogenesis of pulmonary fibrosis. The expression level of the autophagy protein p62 in the lung tissue of IPF patients is greater than that in normal individuals ( 31 ). When autophagy is inhibited, AICAR (an AMPK activator) is unable to reduce the steady-state levels of collagen induced by TGF-β1 ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Procyanidin A1 alleviates acute DSS colitis by regulating AMPK/ mTOR/p70S6K-mediated autophagy (H. Zhang et al, 2022) Fibroblast autophagy in fibrotic disorders requires a fine balance, because an excessive autophagy favours cell survival and differentiation/activation (Del Principe et al, 2013). In this line, Yu and collaborators (Yu et al, 2022) have demonstrated the profibrotic role of autophagy as a mediator of the activation of intestinal fibroblasts (Table 3). Using a DSS fibrosis model and in vitro studies with primary intestinal fibroblasts, their work shows that Caveolin-1 (CAV1) increases the expression of SQSTM1/p62 and TABLE 1 miRNAs related with IBD pathology through modulation of autophagy.…”
Section: Autophagy and Cellular Mediators Of Ibd Fibrosismentioning
confidence: 93%
“…The role of autophagy in IBD-related intestinal fibrosis is controversial. Many studies suggest it has a protective effect (Holvoet et al, 2017;Cosin-Roger et al, 2019), while others have pointed to the harmful role of excess autophagy in fibrotic processes (Yu et al, 2022). The following section will review the evidence for the role of autophagy in intestinal fibrosis at the genetic, cellular, and molecular levels.…”
Section: Relevance Of Autophagy In Ibd Fibrosismentioning
confidence: 99%